Reduced circulating Tregs and positive pANCA were robustly associated with the occurrence of antiphospholipid syndrome in patients with systemic lupus erythematosus. (May 2023) - Wang, Jia; Guo, Hong-Xia; Cheng, Ting; Shi, Lei; Zhang, Sheng-Xiao; Li, Xiao-Feng
Background: Systemic lupus erythematosus (SLE) is a typical chronic immune disorder with clinical heterogeneity. The systemic abnormal immune response not only challenges the diagnosis and treatment of the disease itself but also the secondary antiphospholipid syndrome (APS), characterized by recurrent arterial or venous thrombosis, recurrent spontaneous abortion, or stillbirth. Clinical interest has primarily focused on primary APS's pathological and clinical features. However, differences in clinical features and laboratory indicators between SLE with or without APS are still lacking, especially differences between circulating lymphocytes, which are critical in the pathogenesis of SLE and its complications. Methods: In this retrospective study, we collected and analyzed clinical characteristics, general laboratory indicators, immunological indicators, and circulating lymphocyte subsets of SLE with or without APS. Results: Systemic lupus erythematosus with APS (SLE-APS) had elevated SLEDAI scores, hospitalization costs and time, and frequencies of central nervous system symptoms and spontaneous abortion compared with those without APS. SLE-APS had higher positive anti-Cardiolipin antibodies, anti-β2 Glycoprotein 1 antibodies, and perinuclear antineutrophil cytoplasmic antibody (pANCA) than none-APS patients. Compared with healthy controls (HCs), the circulating lymphocyte subsets were altered to some extent in all patients, especially in patients with SLE-APS. Reduced Tregs and positive pANCA were independent risk factors for SLE secondary APS. Conclusion: The present study revealed a robust association between APS secondary to SLE and reduced Tregs and positive pANCA, which provides essential information regarding the diagnosis and therapeutic possibilities of APS secondary to SLE.